Relativity matters : from Einstein's EMC2 to laser particle acceleration and quark-gluon plasma : with exercises, examples and discussions /: from Einstein's EMC2 to laser particle acceleration and quark-gluon plasma : with exercises, examples and discussions. (2017) - Rafelski, Johann
No abstract available